SISTEM PERIZINAN LINGKUNGAN HIDUP DALAM UU NO. 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Ni Pande Putu Desi Astriani; Made Suksma Prijandhini Devi Salain (Kertha Negara : Journal Ilmu Hukum, 2015)
The paper entitled Permission System of Living Environment through Act Number 32 of 2009 on the Protection and Management of Living Environment. This paper uses analytical normative method and normative legislation approach. The quality of living environment which keep decreasing has been threatening the survival of human beings and other living things so the protection and management of living environment is needed. The permission of living environment plays an important role to protect and manage the environment. Furthermore, this paper will discuss the permission system of the living environment and the factors causing the revocation of living environment permission.